Synthesis of the new 2-(3,4-dihydro-3-oxo-2H-[1,2,4]triazino[4,3-c]quinazolin-4-yl) acetic acid derivatives and analysis of their antioxidant activity in nitrosative stress models - Belenichev, I. F.; Gorchakova, N.; Puzyrenko, A.; Kovalenko, S. I.; Bukhtiayrova, N. V.; Бєленічев, Ігор Федорович; Коваленко, Сергій Іванович; Бухтіярова, Ніна Вікторівна (My University, 2018)
Today we know that NO· and ONOO- are clue pathophysiological factors for progression some ischemic diseases of the central nervous system. So investigation of the antioxidants which will be able to decrease NO· and ONOO- toxicity seems to be very of current interest. The six esters and three amides of 2-(3,4-dihydro-3-oxo-2H-[1,2,4]triazino[4,3-c]quinazolin-4-yl)acetic acid were synthesized for this study, and we showed evidence of antioxidant activity of these new original derivatives. We studied the effect of 2-(3,4-dihydro-3-oxo-2H-[1,2,4]triazino[4,3-c]quinazolin-4-yl)acetic acid derivatives on superoxide dismutase activity under the condition of excessive NO· and ONOO- production. NO· induction was performed by the action of light on sodium nitroprusside Na2[Fe(NO)(CN)5]×2H2O in vitro. Also, the investigation of the substances was carried out in the brain supernatant obtained from the white Wistar rats in vivo. For nitrosative stress modeling dinitrozolic complex of Fe2+ and cysteine were utilized. Our data showed that 2-(3,4-dihydro-3-oxo-2H-[1,2,4]triazino[4,3-c]quinazolin-4-yl)acetic acid is not active compound while its esters and amides have antioxidant activity. Compound benzyl ester of this acid revealed the most effective antioxidant activity.
Keywords: quinazoline derivative; antioxidant; nitrosative stress; neuroprotection